Vitamin D Status in Acute Ischemic Stroke: Relation To Initial Severity and Short-Term Outcome - Sarwar, Natasha; Raja, Khalid Mehmood; Uruj, Sana; Khan, Sarah; Hussain, Amina (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the vitamin D levels among patients presenting with acute ischemic stroke and relationship of these levels with short-term outcome and the severity of stroke.Study Design: Cross-sectional study.Place and Duration of Study: Department of Medicine, Pak Emirates Military Hospital Rawalpindi Pakistan, from Dec 2019 to Feb 2021.Methodology: A total of 300 patients with ischemic stroke diagnosed by the consultant medical specialist or neurologist on the basis of clinical and neuro-radiological findings were included in this study. Serum Vitamin D levels were assessed along with other baseline investigations among the study participants. Severity of stroke was assessed via National Institutes of Health Stroke scale and short-term outcome was assessed by modified Rankin scale.Results: Out of 300 patients of acute ischemic stroke, 183 (62.3%) were males while 117 (37.3%) were females. 151 (50.3%) of the patients had Vitamin D levels within range while 149 (49.7%) had deficient vitamin levels. On National Institutes of Health Stroke scale, 163 (54.3%) had mild, 87 (29%) had mild to moderately severe, 33 (11%) had severe and 17 (5.7%) had very severe symptoms. Statistical analysis revealed that short-term outcome and stroke severity had a statistically significant relationship (p-value